Does person organization fit and person-job fit mediate the relationship between public service motivation and work stress among U.S. federal employees? - Leonard Bright (Administrative Sciences, 2021)
A plethora of research has extolled the benefits of public service motivation (PSM) in public organizations. However, much less empirical attention has focused on its relationship to work stress. Even though it has been theorized that high levels of PSM causes individuals to be more resilient in stressful public service work environments, empirical research has failed to provide support. Only one study has been conducted which has revealed that high levels of PSM is directly associated with high levels of job stress among public employees, but that its beneficial effects are partially mediated by person-organization (PO) fit. That is, employees with high levels of PSM and high levels of fit to their organizations did not appear to suffer from high stress. This study sought to add to this limited body of research and explore the extent to which person-job (PJ) improves the field's understanding of the relationships among PSM, PO fit, and work stress. Based on a sample of federal employees in the United States, this study challenged and confirmed the findings of existing research. For instance, PSM had no direct relationship to work stress. However, PSM maintained an indirect relationship to stress through PO fit. The respondents with high levels of PSM reported that they had high levels of fit to their organizations which was associated with significantly lower levels of work stress. Similarly, PSM was not directly related to PJ fit, but was indirectly related through its association with PO fit. PSM was associated with high levels of fit between employees and public organizations, which was subsequently associated with high levels of fit with public service jobs and lower work stress. Above all, this research clarifies the process of how PSM influences work stress among public employees, through PO fit and PJ fit.
Keywords: 350; person-job fit; person-organization fit; public management; public service motivation; work stress